Exploring virtual encounters in early childhood education: Results of a pilot study - Heide K. Lukosch; Cara Swit; Rene Novak; E. Jayne White (Computers & Education: X Reality, 2025)
Interpersonal skills such as empathy, intuition and sensing, emotional intelligence, and effective communication, are crucial for teachers working with infants (aged birth to 2 year) in Early Childhood Education and Care (ECEC). However, due to the intimate and vulnerable nature of this relationship for infants, opportunities for students to rehearse these skills in real life ECE contexts are limited. We co-designed an immersive virtual reality (VR) environment to simulate an ECEC context, with a virtual baby prototype, furniture such as a changing table and a cot, and toys a user could interact with. A pilot user study tested its efficacy with 17 participants made up of 12 students of a tertiary ECE program and 5 qualified ECE teachers. A questionnaire was used to collect data on usability, experience, and overall feedback on the VR baby experience. Results show that - while the majority of the participants appraised the audio-visual component of the VR environment, the limited haptic feedback and interaction options were a source of fear and discomfort. Participants reported to being immersed in the learning environment, but would appreciate more realistic feedback mechanisms like touch and breath. We suggest that further research looks into the effect of advanced haptic feedback in VR when used for learning in ECE.